Genome-wide CRISPR-based screen identifies E2F transcription factor 1 as a regulator and therapeutic target of aristolochic acid-induced nephrotoxicity - Ziqi Liu; Huan Gao; Guoliang Li; Yongjiang Yu; Mengxing Cui; Honghao Peng; Xinchao Guan; Xue Zhang; Zhihan Zhang; Xiaoyu Shen; Shen Chen; Daochuan Li; et al. (Environment International)
Aristolochic Acid I (AAI) is widely present in traditional Chinese medicines derived from the Aristolochia genus and is known to cause significant damage to renal tubular epithelial cells. Genome-wide screening has proven to be a powerful tool in identifying critical genes associated with the toxicity of exogenous substances. To identify undiscovered key genes involved in AAI-induced renal toxicity, a genome-wide CRISPR library screen was conducted in the human kidney-2 (HK-2) cell line. Among the altered sgRNAs, a significant enrichment of those targeting the E2F transcription factor 1 (E2F1) gene was observed in surviving HK-2 cells in the AAI-treated group. Interestingly, the role of E2F1 had not been previously explored in studies of AAI nephrotoxicity. Further investigations revealed that E2F1 promotes apoptosis by activating the p53 signaling pathway and upregulating pro-apoptotic genes, such as BAK and BAX. Additionally, using the high-throughput experiment- and reference-guided database of traditional Chinese medicine (HERB), cannabidiol (CBD) was identified as an inhibitor of E2F1 by suppressing the activity of NF-κB pathway. In vitro and in vivo models confirmed that CBD inhibits AAI-induced upregulation of E2F1, thereby suppressing p53-mediated apoptosis. In conclusion, this study highlights the crucial role of E2F1 in AAI-induced renal cell apoptosis and identifies CBD as a novel therapeutic candidate for mitigating AAI nephrotoxicity.